Genetic polymorphisms of immune checkpoint proteins PD-1 and TIM-3 are associated with survival of patients with hepatitis B virus-related hepatocellular carcinoma - Li, Zhu (Oncotarget, 2016)
Programmed cell death protein 1 (PD-1) and T-cell immunoglobulin domain and mucin domain containing molecule 3 (TIM-3) are involved in hepatitis B virus (HBV) infection and hepatocellular carcinoma (HCC). This study examined the associations of PD1 and TIM3 polymorphisms with the overall survival (OS) of a prospective cohort of 258 HBV-related HCC patients. Results showed that PD1 +8669 G allele-containing genotypes or TIM3 −1516 genotype GG were significantly associated with longer OS (P < 0.001 and P = 0.001, respectively). In multivariate analysis, PD1 +8669 G allele-containing genotypes and TIM3 −1516 genotype GG were independently associated with longer OS (hazard ratio (HR), 1.835; 95% confidence interval (CI), 1.342–2.509; P < 0.001 and HR, 2.070; 95%CI, 1.428–3.002; P < 0.001, respectively). PD1 +8669 G allele-containing genotypes were significantly associated with longer OS in patients receiving surgical (resection or radiofrequency) treatment, transcatheter arterial chemoembolization (TACE) or supportive and symptomatic treatment. TIM3 −1516 genotype GG was significantly associated with longer OS in TACE patients. In multivariate analysis, PD1 +8669 G allele-containing genotypes were independently associated with longer OS in each treatment population. TIM3 −1516 genotype GG was independently associated with longer OS in patients receiving surgical treatment or TACE. These findings suggest that PD1 +8669 A/G and TIM3 −1516 G/T polymorphisms may affect the prognosis of HBV-related HCC and may be new predictors of prognosis for HCC patients.